2001
DOI: 10.1097/00006534-200108000-00037
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Cardiovascular Risk Profile with Large-Volume Liposuction: A Pilot Study

Abstract: There is general agreement that when discussing surgery with the prospective rhinoplasty patient, one may also include discussion of the chin because of the important interrelationship between these two regions. It is apparent that on the profile-lateral view, the four prominences-the forehead, nose, chin, and neck-balance and complement one another. The cervical region, the fourth dimension, was examined to estimate the aesthetic significance of the nasal-to-cervical relationship and to determine the implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
0
21
0
2
Order By: Relevance
“…Recently, several attempts have been made to improve the metabolic profile of obese subjects by surgically removing certain quantities of subcutaneous or omental fat [53][54][55][56][57][58]. However, the outcomes of these studies have been inconsistent.…”
Section: What Do We Learn From Body Fat Distribution?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several attempts have been made to improve the metabolic profile of obese subjects by surgically removing certain quantities of subcutaneous or omental fat [53][54][55][56][57][58]. However, the outcomes of these studies have been inconsistent.…”
Section: What Do We Learn From Body Fat Distribution?mentioning
confidence: 99%
“…However, the outcomes of these studies have been inconsistent. Removal of a large volume of abdominal subcutaneous fat has yielded improved [54][55][56], unchanged [57] or deteriorated [58] carbohydrate and lipid metabolism. Although promising long-term improvements in fasting plasma glucose and insulin, glucose tolerance and insulin sensitivity have been reported by a study that combined omentectomy with adjustable gastric banding, the metabolic benefits that may have been provided by the reduction of visceral fat may be complemented by the potential reduction in average adipose cell size and, hence the fat mass of all the depots, through the gastric banding [53,59].…”
Section: What Do We Learn From Body Fat Distribution?mentioning
confidence: 99%
“…[10][11][12][13][14] It has been proposed that lower body subcutaneous adipose tissue (LBSAT) functions as a "metabolic sink," storing lipids that might otherwise lead to disturbances in nonadipose tissues. 15 Although metabolic outcomes associated with LBSAT removal in humans have been investigated, [16][17][18][19][20] the "metabolic sink" postulate has not been systematically examined, in part, due to inherent experimental limitations in humans. Large volume reduction of LBSAT, via liposuction, does not alter insulin sensitivity or circulating markers of inflammation in humans.…”
Section: Introductionmentioning
confidence: 99%
“…21 The lack of effect following liposuction, however, may be related to the fact that subjects were morbidly obese prior to and after the procedure. Other studies that have either concluded that liposuction was with 19,20 or without effect [16][17][18] were also confounded by wide variations in BMI (24 to 50), age (18-50 C years), duration of study (12 weeks to years) and amount of adipose tissue removed (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). [16][17][18][19][20] Although liposuction/lipectomy remains a useful tool to evaluate the role of LBSAT in relation to metabolic abnormalities, human data remains inconsistent due, in part, to variability in experimental approach and study populations.…”
Section: Introductionmentioning
confidence: 99%
“…From Sharon GieseÕs excellent work on large-volume liposuction patientÕs it is clear that removing a significant amount of body fat by any means will beneficially modulate the metabolic parameters [1,2].…”
mentioning
confidence: 99%